1999
DOI: 10.1093/nar/27.18.3720
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mammalian RNA polymerase I holoenzyme containing components of the DNA repair/replication system

Abstract: Traditional models for transcription initiation by RNA polymerase I include a stepwise assembly of basic transcription factors/regulatory proteins on the core promoter to form a preinitiation complex. In contrast, we have identified a preassembled RNA polymerase I (RPI) complex that contains all the factors necessary and sufficient to initiate transcription from the rDNA promoter in vitro. The purified RPI holoenzyme contains the RPI homolog of TFIID, SL-1 and the rDNA transcription terminator factor (TTF-1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…In that regard, Hannan et al identified a preassembled RNA polymerase I holoenzyme complex that contains all the factors necessary to initiate transcription of ribosomal DNA. PCNA was detected along with other proteins associated with DNA replication/repair, including Ku 70/80, Top I, TFIID, SL-1, and ribosomal DNA transcription terminator factor (49). This supports our earlier finding that PCNA first appears in nucleoli in early G 1 phase, soon after mitogenic stimulation (4).…”
Section: Discussionsupporting
confidence: 90%
“…In that regard, Hannan et al identified a preassembled RNA polymerase I holoenzyme complex that contains all the factors necessary to initiate transcription of ribosomal DNA. PCNA was detected along with other proteins associated with DNA replication/repair, including Ku 70/80, Top I, TFIID, SL-1, and ribosomal DNA transcription terminator factor (49). This supports our earlier finding that PCNA first appears in nucleoli in early G 1 phase, soon after mitogenic stimulation (4).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown PCNA to be involved in numerous cellular functions associated with cell proliferation and to directly bind to or interact with various proteins, as listed in Table 1 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)24). Our previous study (24) revealed that the PCNA multiprotein complexes purified by mAb to PCNA contained components of multiprotein machinery such as the DNA replication fork (Figure 1) (12,13,21,22) and a quaternary PCNA/ p21/CDK/cyclin complex reported to play a key role in the regulation of the cell cycle (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…It is now known, moreover, that the proteins binding to PCNA are not limited to enzymes involved in the mechanics of DNA replication and repair (13) but also include molecules associated with cell cycle regulation, including p21, cyclin D, and Gadd45 (14)(15)(16)(17). In addition, PCNA interacts with human DNA-(citosine-5) methyltransferase (MCMT), a protein associated with DNA methylation (18), chromatin assembly factor 1, an essential factor for the coupling of chromatin assembly (19), and Ku 70/80, topoisomerase I (topo I), transcription factor IID, SL-1, and ribosomal DNA (rDNA) transcription terminator factor 1, all of which are associated with a preassembled RNA polymerase I holoenzyme complex necessary to initiate transcription of rDNA (20). It also has been observed that the proteins interacting with PCNA can be purified by PCNA-Sepharose 4B affinity chromatography (21), and by the combination of a series of centrifugations, polyethylene glycol precipitation, Sepharose Q column chromatography, and sucrose gradient centrifugation (22).…”
mentioning
confidence: 99%
“…The immunopurified and coimmunopurified proteins were fractionated by SDS-PAGE and analyzed with either anti-FLAG antibodies (FLAGSMRrn3) or with anti-V5 antibodies (V5-TAF I 68). TAF I 68 coimmunoprecipitated with the mutant (lane 4) form of Rrn3 but not with anti-FLAG beads alone (25). Ippt., immunoprecipitate.…”
Section: The Dna Binding Domain Of Human Rrn3 Is Required For Complemmentioning
confidence: 98%
“…The mechanism by which RNA polymerase I is recruited to the committed template is still not completely understood. It has been reported that RNA polymerase I can interact with both UBF and SL1 (25,26). It was established (27) that only ϳ2% of the RNA polymerase I molecules in exponentially growing yeast cells are capable of promoter-specific transcription.…”
mentioning
confidence: 99%